“HEGA”: the Basque version of the PaBiQ parental questionnaire, for clinicians and educators working in the Basque multilingual environment - Pourquié, Marie; Etxeberria, Urtzi; Lacroix, Hugues; Prévost, Philippe (Frontiers in Psychology, 2024)
In this paper, we investigate the relevance of using a parental questionnaire (HEGA) to gather information on children’s language experience in Basque and early language development in order to better interpret language performance in that language. Both this questionnaire and use of language assessment in Basque are needed in the Basque Country, where multilingualism is well attested. The questionnaire was developed after the PaBiQ with additional questions meant to reflect the Basque context, notably its schooling linguistic model. The HEGA was administered to the parents of 186 bilingual children of the Northern Basque Country (age 4;2–9;1) whose language skills in Basque were assessed via a new test battery targeting different linguistic domains (HIGA). Several significant correlations were found between exposure to, and use of Basque and performance in lexical and morphosyntactic production and comprehension. Mixed-effect regression analyses revealed that language experience in Basque, and particularly the fact of being schooled entirely in Basque, were strong predictors of lexical and morphosyntactic outcomes. In contrast, phonological performance, as measured by nonword repetition, appeared to be less impacted by language experience in Basque. Finally, two children were identified as being at risk of language impairment, due to low language performance in Basque despite extended language experience. These results have important implications for clinicians and educators, in particular for detecting language difficulties in Basque-speaking bilingual children. They also show the need for assessing language abilities in Basque for children growing up in a solid Basque-speaking environment.